PERAN MEDIA PEMBELAJARAN IMPLEMENTASI KURIKULUM MERDEKA DI SDN KUIN CERUCUK 4 - Cahya Yasita Dewi; Amanda Zaiti; Jauhar Latipah; Rosvania Wibisono (STKIP Subang, 2025)
This study aims to analyze the role of learning media in supporting the implementation of the Independent Curriculum at SDN Kuin Cerucuk 4. The Independent Curriculum is an educational policy that emphasizes learning independence, learning differentiation, and character building through the Pancasila Student Profile. In practice, learning media has a very important role in creating an interactive, contextual, and meaningful learning process. This study uses a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation studies. The results of the study revealed that the use of appropriate and innovative learning media can increase student participation, strengthen understanding of the material, and support the achievement of learning objectives in accordance with the principles of the Independent Curriculum. However, there are several challenges encountered, such as limited facilities and infrastructure, and the need to improve teacher competence in designing and implementing learning media effectively. Therefore, ongoing training support for educators is very important in optimizing the implementation of this curriculum.